Neurourologic dysfunction: evaluation, surveillance and therapy. Issue 4 (July 2016) - Harris, Catherine J.; Lemack, Gary E.
Abstract : Purpose of review: Neurogenic bladder dysfunction results from a variety of neurologic pathologies and can lead to significant patient morbidity and mortality. This article reviews the evaluation, surveillance and management of patients with spinal cord injury, multiple sclerosis, spina bifida and Parkinson's disease. Recent findings: Recent studies of patients with neurogenic bladder have highlighted their risk for potentially preventable urologic complications ranging from renal failure to urinary tract infections. However, these same studies bring attention to the lack of compliance and consensus regarding the recommended evaluation of these high-risk patients. Summary: Patients with neurovesical dysfunction must be followed at regular intervals to preserve upper tract function, maintain safe bladder pressures, prevent urinary tract infections and address continence. Future studies and guidelines are needed to direct the management of these complicated patients.